2015
DOI: 10.1186/s12871-015-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive perineural bupivacaine attenuates the maintenance of mechanical and cold allodynia in a rat spinal nerve ligation model

Abstract: BackgroundNeuropathic pain is evasive to treat once developed, however evidence suggests that local administration of anesthetics near the time of injury reduces the development of neuropathic pain. As abnormal electrical signaling in the damaged nerve contributes to the initiation and maintenance of neuropathic pain, local administration of anesthetics prior to injury may reduce its development. We hypothesized that local treatment with bupivacaine prior to nerve injury in a rat model of spinal nerve ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…5) in agreement with previous studies. 26 In vivo intracellular voltage recordings in normal and SNA rats…”
Section: Sna Rats Exhibit Behavioral Signs Of Mechanical Heat and Cmentioning
confidence: 99%
“…5) in agreement with previous studies. 26 In vivo intracellular voltage recordings in normal and SNA rats…”
Section: Sna Rats Exhibit Behavioral Signs Of Mechanical Heat and Cmentioning
confidence: 99%
“…However, an attempt at local anesthesia during or immediately following injury has been postulated as a treatment strategy [ 9 , 10 ]. Clifford et al [ 11 ] reported that preemptive local anesthetic attenuates the maintenance of mechanical allodynia in a rat SNL model. Thus suggesting that locally administering anesthetics, such as lidocaine, bupivacaine, and ropivacaine, close to the time of injury, reduces the development of neuropathic pain [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was thus selected for use in this study. Previous studies have reported that if pathological activity following injury is blocked by local anesthetics, allodynia may not develop [ 9 11 ]. Using local anesthetics following nerve damage can be considered a treatment strategy for such pain.…”
Section: Introductionmentioning
confidence: 99%